2008
DOI: 10.1091/mbc.e07-07-0633
|View full text |Cite
|
Sign up to set email alerts
|

The Human Spindle Assembly Checkpoint Protein Bub3 Is Required for the Establishment of Efficient Kinetochore–Microtubule Attachments

Abstract: The spindle assembly checkpoint monitors the status of kinetochore-microtubule (K-MT) attachments and delays anaphase onset until full metaphase alignment is achieved. Recently, the role of spindle assembly checkpoint proteins was expanded with the discovery that BubR1 and Bub1 are implicated in the regulation of K-MT attachments. One unsolved question is whether Bub3, known to form cell cycle constitutive complexes with both BubR1 and Bub1, is also required for proper chromosome-to-spindle attachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
104
1
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(127 citation statements)
references
References 65 publications
13
104
1
9
Order By: Relevance
“…Depletion of Bub3 produced a severe defect in nocodazole-induced, chronic mitotic checkpoint signaling ( Fig. S1 A and B), as expected from prior work (23). The BubR1 E409K variant with a defect in Bub3 binding gave rise to extensive chromosome misalignment yet failed to delay anaphase onset in an unperturbed mitosis ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Depletion of Bub3 produced a severe defect in nocodazole-induced, chronic mitotic checkpoint signaling ( Fig. S1 A and B), as expected from prior work (23). The BubR1 E409K variant with a defect in Bub3 binding gave rise to extensive chromosome misalignment yet failed to delay anaphase onset in an unperturbed mitosis ( Fig.…”
Section: Resultssupporting
confidence: 81%
“…Bub3 was identified as a mitotic checkpoint protein through genetic screening in budding yeast (19), and subsequent work in higher eukaryotes also demonstrated a profound defect in this checkpoint in the absence of Bub3 (20)(21)(22)(23). Recently, Bub3 has been shown to bind the phospho MELT motif on KNL-1 for kinetochore localization of Bub1 (budding uninhibited by benzimidazole 1), disruption of which caused a defective checkpoint (24)(25)(26)(27) with Bub1 binding to kinetochores apparently required for binding of other checkpoint proteins (28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…Logarinho et al (54) confirmed and extended these results. They showed that 10 -30% of cells depleted of Bub1, Bub3, and BubR1 at metaphase had more than four misaligned chromosomes.…”
Section: Promoting Proper Kinetochore-microtubule Attachment By Spindmentioning
confidence: 72%
“…49,71,72 The next proteins that bind to kinetochors are Bub3 and BubR1 (mammalian homolog of yeast Mad3). 73 As a platform, Bub3 associates with Mad2, Mad3 and Cdc20, which directly inhibit anaphase promoting complex/cyclosome (APC/C). 74,75 BubR1 is required for kinetochore loading of Mad1 and Mad2.…”
Section: Reviewmentioning
confidence: 99%